(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
A black, few centimeters thick Marker-bed of Holocene age is consistently recorded in all the deep-sea cores raised from two ﬁelds of mud diapirs recently discovered on the crest of the Mediterranean Ridge south of Crete. Detailed investigations on the ultrastructure of the Marker-bed accompained by micro-probe analysis revealed the occurrence of Mn-rich micronodules and bacterial colonies in very high number. Their occurrence is accounted to ﬂuid escape in the accretionary prism, related to mud diapirism and tentatively associated with an important volcanic event occurred in the arc-trench system.